The KARAKTERISASI PLASTIK PENGEMAS MAKANAN DARI TEPUNG MAIZENA DAN BATANG PISANG - SISKA OKTORINA SIMBOLON (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
Edible films as food wrapping plastics made from corn starch and plasticizers as result of liquefaction of banana stem are prepared to evaluate the effect of adding plasticizers on mechanical characteristic, functional groups, and water resistance. The starch formulation: plasticizer that is used in this research is 4: 0, 4: 2, 4: 3, 4: 4, 4: 5, 5: 0, 5: 2, 5: 3, 5: 4, 5: 5, 6: 0, 6: 2, 6: 3, 6: 4, 6: 5, 7: 0, 7: 2, 7: 3, 7: 4, 7: 5 (gr / gr), the size of banana stem for the liquefaction process passes 200 mesh sieve and the time for stirring the process of making edible film is 30 minutes at 135 rpm. To find out the characteristics of edible film, several analyzes were carried out, such as mechanical characteristic test (tensile strength, percent elongation and modulus young), water absorption and FTIR. The highest tensile strength, elongation and the highest modulus young in this research were obtained in starch: plasticizer formulations in a row of 6: 0, 7: 5, and 4: 0, with values ​​of 16.76 MPa, 14.29% and 511.34 Mpa. Films with these values ​​are in accordance with edible film standards. Adding the liquefaction plasticizer also affects the water resistance of the film, where the more plasticizer is added, the less water is absorbed by the film. The results of the analysis with FTIR showed that the wavelength did not change significantly. It means that the result of starch film is a physical blending process because no new functional groups were found.